EFEKTIVITAS MANAJEMEN HUMAS DALAM MEMBANGUN CITRA PENDIDIKAN UNIVERSITAS ISLAM NEGERI AR-RANIRY BANDA ACEH - Abdullah Munir (Intelektualita, 2023)
Public Transportation has an important position in advancing an institution or agency or company, as a liaison between institutions and the community as users of institutional services. The purpose of this investigation is to explain the effectiveness of public transportation management in the field of student affairs, supported by the leadership role at Ar-Raniry State Islamic University, Banda Aceh, and analyze the achievement of the expected public transportation management process. Collecting data using interview techniques and methods, and with a qualitative approach the results are explained. The data collection tool uses observational guide sheets and interview guide lines, as well as the results of documentation analysis. The results of the first study, there is good cooperation from all educators and education residents as well as the management, especially public transportation so that there is good communication to students and the community; and second, the realization of tangible results with the role and support of a good leader and if public relations carry out their duties perfectly according to the program that has been structured.